2015
DOI: 10.5455/ovj.2015.v5.i1.p11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of several methods of sires evaluation for total milk yield in a herd of Holstein cows in Yemen

Abstract: A total of 956 lactation records of Holstein cows kept at Kaa Albon station, Imuran Governorate, Yemen during the period from 1991 to 2003 were used to investigate the effect of some genetic and non-genetic factors (Sire, parity, season of calving, year of calving and age at first calving as covariate) on the Total Milk Yield (TMY), Lactation Length (LL), and Dry Period (DP). Components of variance for the random effects (mixed model) were estimated by Restricted Maximum Likelihood (REML) methodology. Sires we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…It is observed that the cows exhibit variations in their milk production and milkingability characteristics from year to year. Similar results for all studied traits stated by (Al-Samarai et al, 2015, Faid-Allah, 2015Awady et al, 2016;Koc, 2017;and Hadad, 2020) for milk production traits and in accordance with for milking-ability traits for Holstein dairy cattle in South African (Tshilate, 2017).…”
Section: Table 2 Genetic Factors Affect Milk Production and Milking-a...supporting
confidence: 85%
See 1 more Smart Citation
“…It is observed that the cows exhibit variations in their milk production and milkingability characteristics from year to year. Similar results for all studied traits stated by (Al-Samarai et al, 2015, Faid-Allah, 2015Awady et al, 2016;Koc, 2017;and Hadad, 2020) for milk production traits and in accordance with for milking-ability traits for Holstein dairy cattle in South African (Tshilate, 2017).…”
Section: Table 2 Genetic Factors Affect Milk Production and Milking-a...supporting
confidence: 85%
“…The inclusion of parity as a fixed effect had a remarkably significant influence (P≤0.01) on 305-day milk yield and a significant impact (P≤0.05) on average flow rate, peak milk flow rate, and milk duration (Table 3). Table (3) displays a highly significant on 305-dMY and this result is in accordance with (Atil, 2000); (Tadesse et al, 2010;(Usman et al, 2012;Chegini et al, 2015;Al-Samarai et al, 2015;Faid-Allah, 2015;Mikó et al, 2016;Hammoud, 2016a, andKoc, 2017). Also, parity has a significant effect on AFR, PF and MD this result is in accordance with (Petersen et al, 1986;Sandrucci et al, 2007;Gäde et al, 2007;Guler et al, 2009;Antalík andStrapák, 2011, andBerry et al, 2013).…”
Section: Table 2 Genetic Factors Affect Milk Production and Milking-a...supporting
confidence: 64%
“…Some previous researches report the average production per lactation. At the Kaa Alboon Station, Imuran Governorate, Yemen was 3919.66±42.99 kg (Samarai et al, 2015); at BPPT-SP Cikole Lembang was 4558±1326 kg (Anggraeni et al, 2008); in West Java was 4185.89±990.43 kg (Makin and Suharwanto, 2012); at the Government Dairy Farm Quetta, in Balochistan province, Pakistan was 3977.75±37.20 (Sandhu et al, 2011). By comparing these results, it can be assumed that the average value of milk production is categorized as medium milk production capability.…”
Section: Milk Production Per Lactationmentioning
confidence: 99%
“…Milk sales represent the largest proportion of income in a dairy farm, making milk production the major factor influencing the net return. Fertility traits such as age at first calving (AFC), inter-calving period (ICP), and days open (Bajwa et al, 2004;Kunaka & Makuza, 2005;Pirzada, 2011;Nyamushamba et al, 2014;Al-Samarai et al, 2015) greatly affect milk production. Prolonged intervals in these traits are a constraint to farm profitability because of the high maintenance costs of non-productive animals (Muller, 2017).…”
Section: Introductionmentioning
confidence: 99%